Growth and Characterization of Gamma Glycine Single Crystal from Ammonium Sulfate as Solvent - S. Ganesan, S. Anbuchudar Azhagan* (Recent Research in Science and Technology, 2010)
Single crystals of Î³-glycine, an organic nonlinear optical material were grown by low temperature solution growth methods from aqueous solutions of glycine and ammonium sulfate. Powder X-ray diffraction of the grown crystal was recorded and indexed. The Î³-phase of glycine is confirmed by powder XRD and FTIR spectroscopy.CHN analysis shows the non-existence of ammonium sulfate species in the grown Î³-glycine single crystals .Optical transmittance spectrum was recorded in the range from 200 to 1100nm.Thermal properties of the grown crystal have been investigated using differential thermal analysis. The NLO property of the crystal was confirmed by Kurtz and Perry technique.